Clinical features and risk factors for development of post-infectious bronchiolitis obliterans in children - Weihan Xu; Xiaohui Wen; Haiming Yang; Jinrong Liu; Xiaolei Tang; Hui Xu; Hui Liu; Huimin Li; Shunying Zhao (BMC, 2024)
Abstract Background Post-infectious bronchiolitis obliterans (PIBO) is a severe form of chronic obstructive lung disease secondary to severe respiratory tract infections. Knowledge of pediatric PIBO development-associated risk factors may improve selection of appropriate early therapeutic interventions. Objective The aim of this study was to describe the clinical characteristics of children diagnosed with PIBO, and identify the risk factors for development of PIBO after adenovirus pneumonia. Methods First, a retrospective observational study was performed of 308 pediatric patients with PIBO (ages < 5 years) that revealed high frequencies of non-invasive/invasive ventilation, co-infection, and atopic conditions. Subsequently, we retrospectively reviewed 131 patients (ages < 5 years) with adenovirus pneumonia who developed BO (included among the 308 children) or not. Logistic regression analysis revealed PIBO development-associated risk factors. Results Respiratory symptoms of 308 patients (median age of 18 months, range: 12-54 months; male predominance of 3.7:1) included wheezing (71%), dyspnea (66%), tachypnea (23%), and hypoxemia (18%). Etiologic agents (predominantly adenovirus, Mycoplasma pneumoniae) were detected in 236 patients, of whom 137 had co-infections. Notably, atopic disease history (of patients and/or family members) was associated with 78% of patients, and 15% of patients diagnosed with asthma before, at the time of PIBO diagnosis. In a subsequent study of 131 adenovirus pneumonia patients, multivariate analysis showed that co-infection (OR 4.20, 95% CI 1.29 to 13.63), atopic conditions (OR 29.67, 95% CI 12.16 to 81.67), and duration of fever (OR 1.42, 95% CI 1.10 to 1.83) were independent risk factors for PIBO development following adenovirus pneumonia. Conclusions Atopic conditions, co-infections, and duration of fever were identified as risk factors for pediatric post-infectious BO development following adenovirus pneumonia, and PIBO may overlap with asthma, warranting early aggressive treatment and further research to elucidate roles of atopic conditions in BO development.